EDUKASI REGULASI EMOSI DAN MANAJEMEN STRES UNTUK MENINGKATKAN KESEHATAN MENTAL DI SMAN 02 SIAK - Nurfitriana; Ghulamzaki Abd Matin; Syantia Artinda; Dipo Oktavian; Putri Andini; Tiara Suci Wulandari; Amelia Br. Sitepu; Vitto Farrell Duta Herlan; Cerah Arsi Habibah; Putri Awalia; Naila Syarifa; Muhammad Akbar; Reza Aditya Pratama Siregar; Candra Meila Intansari (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Mental health and emotional regulation skills are important aspects in supporting the psychological development of adolescents, especially high school students. A lack of understanding of how to manage emotions and maintain mental health often has an impact on declining learning concentration and the quality of students' social interactions. This community service activity was carried out by the Real Work Lecture (KKN) team through the mental health socialization and emotional regulation work program at SMAN 2 Negeri Siak. The purpose of this activity is to increase students' knowledge and awareness of the importance of maintaining mental health and provide practical strategies in managing emotions positively. The method used in socialization includes lectures followed by discussion sessions, questions and answers, and pretest postest to students. The results of the implementation of the activity showed high enthusiasm from the participants, which was marked by active involvement in the question and answer session and increased students' understanding of the material presented. Thus, this socialization activity is expected to make a real contribution to forming a healthier mindset and more adaptive emotional regulation skills among adolescents.